Logistics outsourcing in supply chain management - Ode, Olushola (Cranfield University, 2025)
This study aims to understand the role of logistics service providers in humanitarian operations as well as the support they provide in different disaster types. The study will also formulate a theoretical framework of the logistics services providers’ competencies in disaster relief operations. A systematic literature review was used in planning, searching, selecting, synthesising, analysing and reporting the academic literature on logistics outsourcing in supply chain management. The systematic literature review ensured academic rigor, improving the consistency and reproducibility of the study. Content analysis of 63 peer-reviewed, academic journal articles, with a timeline of 2007 to 2025, was conducted. The descriptive and thematic analyses conducted provide insights into the subject matter. It is evident that logistics service providers play an increasingly significant role in humanitarian operations. Some of these include their support with technical competencies, digital transformation of humanitarian operations, security, network access, cultural intelligence, et cetera. There is, however, the need to establish and maintain partnerships with the humanitarian organisations, pre-disaster. There is also the need to redirect focus and resources towards development efforts as against disaster relief operations to ensure resilient and sustainable structures are in place for better outcomes, post-disaster. The relative heterogeneity of research in managerial studies makes it difficult to conduct aggregate studies, necessitating use of themes to understand the data gathered. The study’s reliance on published data also introduces vulnerabilities concerning the lack of access to granular data the researchers utilised in reaching their findings. This makes it difficult to guarantee fully independent and unbiased suppositions. The focus on English language only publications may imply that the study is not fully representative of the existing body of knowledge on the subject matter. A significant proportion of the existing literature provides a global, often one-size fits all approach with regards to the capabilities needed in the disaster types. This study provides more detail on context-specific nature of the disasters and the need to tailor the response accordingly. Logistics service providers can effectively deliver on their humanitarian objectives through their operational capabilities and strategic partnerships with the humanitarian organisations and the local communities.
Keywords: Humanitarian; emergency response logistics; third party logistics; logistics service providers; disaster relief operations; outsourcing capabilities